Physical fitness development of Brazilian adolescents as a function of age, training status, gender and time of measurement - Böhme, M. T. S.; Bojikian, L. P.; Uezu, R.; Ugrinowitsch, C.; Botter, D. A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The main purpose of long term training is to prepare future generations of athletes; detecting, selecting and promoting sport talents. Thus, the understanding of youth physical fitness' development is an important step to increase the effectiveness of the preparation process. The purpose of this study was to evaluate physical fitness development of Brazilians adolescents from 11 to 14 years old, as a function of gender, age, training status, and time of measurements. Methods The sample was composed of 196 adolescents from 11 to 14 years old. The subjects were divided in four groups according to training status and gender (male trained n=37, female trained n=64, male untrained n=34, female untrained n=51). Horizontal jump (HJ), medicine ball throw (MBT), abdominal muscle endurance, agility, speed (30 m), flexibility (sit and reach) and nine minute run tests were applied at three time points, six months apart. The first evaluation of the training groups was performed immediately before training started. Regression models for dependent measurements were applied having gender, group, age and time of measurement as fixed effects. Subjects were considered as random effects. Age was introduced in the model to control the evolution of the response variables as a function of it. Four models were fitted for each response variable and group. Conclusions All variables presented a linear behavior across time point measurements. In this way, a line was fitted for each group, fixing the age of the subjects. As the trained groups had superior performance than the untrained groups at the first time point measurement, differences between groups could not be attributed to the training process. Female trained girls average values for the agility, abdominal endurance, flexibility, and medicine ball throw varied linearly as a function of age and time measurement. On the other hand, horizontal jump, endurance and speed were a function of age only. In the female untrained group there was no effect of age or time point of measurement for agility, abdominal endurance, horizontal jump, speed and 9 min run tests. The average medicine ball throw increased linearly as function of age, while flexibility increased as a function of the time of measurement. The male trained group presented similar behavior to the female trained group with exception of endurance, which changed as a function of age and time of measurement. The male untrained group increased agility, flexibility, and endurance as a function of age and time of measurement, and ball throw, horizontal jump, and speed as a function of age only. Abdominal endurance did not change across time.